2008
DOI: 10.1002/humu.20789
|View full text |Cite
|
Sign up to set email alerts
|

Mutational spectrum ofFAM83H: the C-terminal portion is required for tooth enamel calcification

Abstract: Dental enamel forms through the concerted activities of specialized extracellular matrix proteins, including amelogenin, enamelin, MMP20, and KLK4. Defects in the genes encoding these proteins cause non-syndromic inherited enamel malformations collectively designated as amelogenesis imperfecta (AI). These genes, however, account for only about a quarter of all AI cases. Recently we identified mutations in FAM83H that caused autosomal dominant hypocalcified amelogenesis imperfecta (ADHCAI). Unlike other genes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 7 publications
5
53
0
Order By: Relevance
“…Previous studies proposed that FAM83H encode a nonsecreted protein due to the absence of a signal peptide [Kim et al, 2008]. In the present study, by running SWISS-MODEL and CPHmodels-3.0, the Nterminal of FAM83H favor a template 1byr, which is the first crystal structure of a PLD family member.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies proposed that FAM83H encode a nonsecreted protein due to the absence of a signal peptide [Kim et al, 2008]. In the present study, by running SWISS-MODEL and CPHmodels-3.0, the Nterminal of FAM83H favor a template 1byr, which is the first crystal structure of a PLD family member.…”
Section: Discussionmentioning
confidence: 97%
“…The expression of FAM83H in many tissues suggests that it functions in many cells throughout the body [Kim et al, 2008;Lee et al, 2009]. The predicted quite different structures for the N-and C-terminals of FAM83H indicate that the two parts could play different roles in different cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another report analyzed the known candidate genes ENAM, AMBN, AMELX, MMP20, KLK4, and amelotin (AMNT) in two Brazilian families by PCR and sequencing and excluded the participation of these genes in the hypomineralized AI phenotype (Santos et al 2007). Surprisingly, at the beginning of 2008, two studies carried out by the same group of researchers reported 6 mutations in the FAM83H gene, found in region 8q24.3, which is responsible for hypocalcified ADAI (Lee et al 2008a). With the recent work of Hart et al (2009), Wright et al (2009), Hyun et al (2009), and El-Sayed et al (2010, the number of mutations in the FAM83H gene has increased to 16 ( Table 1).…”
Section: Phenotype-genotype Correlations In Autosomally Inherited Casesmentioning
confidence: 94%
“…To date, 9 mutations have been reported in the enamelin gene (Table 1) (Rajpar et al 2001;Mardh et al 2002;Kida et al 2002;Hart et al 2003b;Kim et al 2005a;Ozdemir et al 2005a;Gutiérrez et al 2007;Kang et al 2009); 1 mutation has been reported in DLX3, which is responsible for the ADAI cases associated with taurodontism (Dong et al 2005); and 16 mutations have been reported in the recently nominated FAM83H gene. This series of mutations within these three genes are all associated with ADAI of the hypocalcified type (Table 1) Lee et al 2008a;Hart et al 2009, Wright et al 2009Hyun et al 2009;El-Sayed et al 2010).…”
Section: Autosomally Inherited Typesmentioning
confidence: 96%